Effects of Recurrent Selection on Population Structure and Allele Frequencies in the M3S Maize Population - Bukan, Miroslav; Mandić, Ana; Kozumplik, Vinko; Lewis, Ramsey S.; Šimić, Domagoj; Šarčević, Hrvoje (Agriculture (Basel), 2024)
The effects of four cycles of recurrent selection on the allele frequencies of simple sequence repeat (SSR) markers and population structure were examined in the Maksimir 3 Synthetic (M3S) maize population (Zea mays L.). Genotyping of 32 plants from each selection cycle at 38 SSR loci revealed that the mean number of alleles per locus and the mean expected heterozygosity were preserved across selection cycles, indicating the maintenance of sufficient genetic variability in the population required for future genetic gain. The Waples test of selective neutrality revealed that genetic drift was the main force in changing allele frequencies in the population. The proportion of selectively non-neutral loci in single cycles of selection varied between 16% and 37%. Some non-neutral loci shared the same genomic locations with previously published QTLs controlling important agronomic traits. An analysis of molecular variance revealed that 5.6% of the genetic variation occurred among and 94.4% within cycle populations. Between 5% and 29% of loci were found to be in a significant Hardy–Weinberg (HW) disequilibrium, with the majority showing an excess of homozygosity. The excess of homozygosity at several loci was highly consistent across cycle populations, suggesting positive assortative mating as a possible cause of the observed HW disequilibrium. Linkage disequilibrium (LD) tests revealed that the M3S population was essentially in linkage equilibrium. The proportion of pairs of loci in significant LD varied from 0.1% to 1.8% across selection cycles, probably due to the effects of genetic drift and epistatic selection.